Archaeology of the Anthropocene - Edgeworth, Matt; Benjamin, Jeffrey; Clarke, Bruce; Crossland, Zoe; Domanska, Ewa; Gorman, Alice Claire; Graves-Brown, Paul; Harris, Edward Cecil; Hudson, Mark James; Kelly, Jason M.; Paz, Victor Joaquin; Salerno, Melisa Anabella; et al. (Journal of Contemporary Archaeology, 2014)
What role will archaeology play in the Anthropocene – the proposed new geological epoch marked by human impact on Earth systems? That is the question discussed by thirteen archaeologists and other scholars from five continents in this thought-provoking forum. Their responses are diverse and wide-ranging. While Edward Harris looks to archaeological stratigraphy for a material paradigm of the Anthropocene, Alice Gorman explores the extent of human impact on orbital space and lunar surfaces – challenging the assumption that the Anthropocene is confined to Earth. Jeff Benjamin investigates the sounds of the Anthropocene. Paul Graves-Brown questions the idea that the epoch had its onset with the invention of the steam engine, while Mark Hudson uses Timothy Morton’s concept of hyperobjects to imagine the dark artefacts of the future. Victor Paz doubts the practical relevance of the concept to archaeological chronologies, and Bruce Clarke warns archaeologists to steer clear of the Anthropocene altogether, on the grounds of the overbearing hubris of the very idea of the Age of Humans. Others like Jason Kelly and Ewa Domanska regard the Anthropocene debate as an opportunity to reach new forms of understanding of Earth systems. André Zarankin and Melisa Salerno ground significant issues in the archaeology of Antarctica. And Zoe Crossland explores the vital links between the known past and the imagined future. As a discipline orientated to the future and contemporary world as well as the past, Chris Witmore concludes, archaeology in the Anthropocene will have more work than it can handle.